2018
DOI: 10.1097/inf.0000000000001916
|View full text |Cite
|
Sign up to set email alerts
|

Safety, Tolerability and Pharmacokinetics of MEDI8897, an Extended Half-life Single-dose Respiratory Syncytial Virus Prefusion F-targeting Monoclonal Antibody Administered as a Single Dose to Healthy Preterm Infants

Abstract: Background:MEDI8897 is a recombinant human monoclonal antibody being developed for prophylaxis of serious respiratory syncytial virus (RSV) disease in all infants.Methods:In this phase 1b/2a dose-escalation study, healthy preterm infants with a gestational age of 32–35 weeks were randomized to receive a single intramuscular injection of MEDI8897 (10, 25 or 50 mg) or placebo. Safety, pharmacokinetics, RSV-neutralizing antibody and antidrug antibody (ADA) assessments were performed during the 360-day follow-up p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
125
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 175 publications
(129 citation statements)
references
References 25 publications
3
125
0
1
Order By: Relevance
“…59 However, it is the trough concentrations and the half-life that drive FIP dose selection for mAbs, especially those targeted against infectious antigens. 3,19,21 For these products, clinicians seek a dosing regimen that sustains a trough concentration above a target value. In doing so, the patient achieves stronger immunity against the infectious antigen (respiratory syncytial virus, HIV, bacterial antigens, etc).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…59 However, it is the trough concentrations and the half-life that drive FIP dose selection for mAbs, especially those targeted against infectious antigens. 3,19,21 For these products, clinicians seek a dosing regimen that sustains a trough concentration above a target value. In doing so, the patient achieves stronger immunity against the infectious antigen (respiratory syncytial virus, HIV, bacterial antigens, etc).…”
Section: Discussionmentioning
confidence: 99%
“…Adult and pediatric concentration-time profiles featuring intravenous and intramuscular administrations were extracted from the literature for pagibaximab, palivizumab, MEDI8897, and intravenous immunoglobulin (IVIG). 3,[18][19][20][21][22][23][24][25] No adult PK data were available for palivizumab.…”
Section: Pharmacokinetic Datamentioning
confidence: 99%
“…Similarly, individuals with very severe immunodeficiency (right, 2 to 7 criteria; red line) had a higher risk for mortality than those with moderate immunodeficiency (right, 1 criterion, green line) or moderate risk (right, 0 criteria; blue line) (OR, 11.1; 95% CI, 2. Community-Acquired Respiratory Viruses Posttransplant Clinical Microbiology Reviews pharmacokinetics in adults and infants (144,145). Currently, no studies are planned with this compound in immunocompromised patients, but initial studies in otherwise healthy patients are ongoing.…”
Section: Human Pneumo-and Paramyxoviridaementioning
confidence: 99%
“…Comparison of the neutralization potency of two site Ø antibodies, D25 [34] and 5C4 [35], with palivizumab, a site II-directed conformation-independent antibody [36], demonstrated that the prefusionspecific antibodies are 10-100 times more potent [8]. Other potent prefusion-specific human antibodies that bind to the apex of the trimer, such as AM22 and RSD5, have also been isolated in recent years [8,37,38], and one of them (MEDI8897) is now in advanced stages of clinical development [39].…”
Section: Introductionmentioning
confidence: 99%